Resistance status of Aedes aegypti towards different insecticides in selected dengue outbreak area in Petaling district (Diptera: Culicinae) - Noor Aslinda Ummi Awang Besar; Azman Sulaiman; Lailatul-Nadhirah Asri; Khadijah Khairuddin (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2019)
Four field strains of Aedes aegypti from dengue outbreak areas in Petaling, Selangor were evaluated using two groups of insecticide; pyrethroid class II (deltamethrin) and organophosphate (malathion and pirimiphos-methyl). This study was conducted according to the WHO adult mosquito bioassay procedure (WHO/ZIKV/VC/16.1). Results of two-way ANOVA indicated that there was a significant difference resistant levels in type of insecticides used against different localities which were TUDM, Brunsfield, Gugusan Semarak and Apartment Sri Indah (F=57.985, df 6, 48, p<0.05). From the Tukey post-hoc test, it revealed that across different type of insecticides tested, the percentage of mortality in Ae. aegypti was significantly difference (p<0.05) amongst insecticides, viz., deltamethrin, malathion and pirimiphos-methyl. Factor of locality shows significant difference towards percentage of mortality in Ae. aegypti in TUDM and Apartment Sri Indah (p<0.05), but there were no significant difference of percentage of Aedes aegypti mortality in Brunsfield and Gugusan Semarak (p>0.05). Resistance ratio for all the Ae. aegypti from localities selected ranged from 20 fold to 128 fold (moderate resistance and highly resistance categories). Results of this research showed that resistance presence in mosquito populations in the selected dengue outbreak areas in Petaling and that it could the reason controlling dengue is ineffective. We suggest to rotate insecticides with different mode of action and safer insecticides other than pyrethroids plus public awareness to eliminate the mosquitoes breeding places.